2020
DOI: 10.48550/arxiv.2006.09514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Remarks on cosmological bulk viscosity in different epochs

Iver Brevik,
Ben David Normann

Abstract: The intention of this paper is mainly two-fold. First, we point out a striking numerical agreement between the bulk viscosity in the lepton era calculated by Husdal (2016) and our own calculations of the present-day bulk viscosity when the functional form is ζ ∼ √ ρ. From a phenomenological

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…In the recent paper Brevik and Normann [43] have obtained the value of m = 1/2 to be distinguished by the current Universe. We have found that cosmological models with viscous matter and without the cosmological term should be structurally stable provided that the parameter m < 1/2.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent paper Brevik and Normann [43] have obtained the value of m = 1/2 to be distinguished by the current Universe. We have found that cosmological models with viscous matter and without the cosmological term should be structurally stable provided that the parameter m < 1/2.…”
Section: Discussionmentioning
confidence: 99%
“…Obtained in such a way fluid with negative pressure we called viscous dark mater. We assume that the viscosity coefficient is parameterized by the Belinskii-Khalatnikov power law form but in a realistic case the parameterization can depend on the cosmological epoch [17].…”
Section: Introductionmentioning
confidence: 99%